Endolymphatic sac tumor showing increased activity on 68Ga-DOTA-TATE PET/CT - Papadakis, Georgios Z. (Clin Nucl Med, 2016)
Endolymphatic sac tumors (ELSTs) are rare tumors arising from the epithelium of the endolymphatic sac and duct that can be either sporadic or associated with von Hippel-Lindau (VHL) disease. We report a case of a VHL patient with histologically proven residual ELST, who underwent (68)Ga-DOTA-TATE-PET/CT showing increased activity (SUVmax: 6.29) by the ELST. The presented case of a VHL-associated ELST with increased (68)Ga-DOTA-TATE uptake indicates cell-surface expression of somatostatin receptors (SSTR) by this tumor, suggesting the potential application of SSTR-imaging using (68)Ga-DOTA-conjugated-peptides in the work-up and management of these patients.